2017
DOI: 10.1002/2017ja023878
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study of low‐frequency magnetic field fluctuations near Venus during the solar cycle

Abstract: We statistically investigate the solar cycle dependence of the magnetic field fluctuations in the frequency range 30–300 MHz based on Venus Express data. We present the spatial distributions of fluctuation properties during three typical periods of the solar cycle, and a comparative study is also performed. With the increase of solar activity, the magnetic field is still quiet in the magnetotail region and the wave intensity becomes weaker in the magnetosheath. The transverse component of fluctuations becomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
1
12
1
Order By: Relevance
“…A clear increase in the magnetic field strength can be observed at the bow shock in Figures a and b, and the induced magnetosphere and magnetosheath are also indicated in these two panels. Solar cycle variations of the magnetic structures and fluctuation properties near Venus have been reported by previous studies (e.g., Shan et al, ; Xiao et al, ; Xiao & Zhang, ). As shown in Figures e and f, the noisy fluctuations appear more in the dayside bow shock and nightside magnetosheath, while turbulence can be observed upstream of the bow shock and the magnetosheath boundary layers containing the nightside bow shock.…”
Section: Statistical Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…A clear increase in the magnetic field strength can be observed at the bow shock in Figures a and b, and the induced magnetosphere and magnetosheath are also indicated in these two panels. Solar cycle variations of the magnetic structures and fluctuation properties near Venus have been reported by previous studies (e.g., Shan et al, ; Xiao et al, ; Xiao & Zhang, ). As shown in Figures e and f, the noisy fluctuations appear more in the dayside bow shock and nightside magnetosheath, while turbulence can be observed upstream of the bow shock and the magnetosheath boundary layers containing the nightside bow shock.…”
Section: Statistical Resultssupporting
confidence: 70%
“…Turbulence and the multiscale energy cascade seem to occur preferentially at the nightside bow shock. Although there are some solar cycle variations in the magnetic field and fluctuations near Venus (e.g., Xiao et al, ; Xiao & Zhang, ), this study shows no clear solar cycle dependence of the spectral scaling features near the Venusian bow shock. This result is clearly indicated in Figure , in which the variations of spectral scaling indices with the SZA exhibit the same trend between solar maximum and minimum.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…The fluctuations convected from the upstream region have been observed by Hoppe and Russell (). Some other studies also suggested that the dayside magnetosheath is filled with strong fluctuations convected from the foreshock and the bow shock (e.g., Du et al, ; Xiao et al, ).…”
Section: Introductionmentioning
confidence: 97%